Copper iodide as a potential low-cost dopant for spiro-MeOTAD in perovskite solar cells. Issue 38 (15th September 2016) - Wang, Peng; Zhang, Jing; Zeng, Zhaobing; Chen, Renjie; Huang, Xiaokun; Wang, Liming; Xu, Jie; Hu, Ziyang; Zhu, Yuejin
Abstract : Low-cost inorganic copper iodide (CuI) is introduced as a potential oxidizer for hole-transport material (HTM) in perovskite solar cells (PSCs). Abstract : Low-cost inorganic copper iodide (CuI) is introduced as a potential oxidizer for hole-transport material (HTM) in perovskite solar cells (PSCs). Characterization of oxidizability and energy levels indicates that the CuI can effectively oxidize spiro-MeOTAD. Through solvent engineering and concentration optimization, the CuI (20% mole ratio) doped spiro-MeOTAD gives higher power conversion efficiency (PCE) than that of the FK209 dopant. This work shows the promise of a state-of-the-art method using a low-cost dopant for hole transport material in perovskite solar cells.